2017
DOI: 10.1159/000455997
|View full text |Cite
|
Sign up to set email alerts
|

Is Imprint Cytology Useful to Diagnose Malignancy for Brenner Tumors? A Case Series at a Single Institute

Abstract: Background: The aim of this study was to investigate cytological features of Brenner tumors according to tumor grade using imprint cytology. Case: Between 2004 and 2015, intraoperative imprint cytology was performed on 8 patients with Brenner tumors suspected to be malignant neoplasmas on gross examination because of their large size and solid part. These consisted of 1 benign, 3 borderline, and 4 malignant tumors. In patients with benign and borderline tumors, naked nucleus-like stromal cells and tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although they can express sex‐cord markers including SF‐1 and FOXL2, 51 they are also usually positive for epithelial and smooth muscle antigens and harbor NCOA1/NCOA2/NCOA3 rearrangements in 81% of cases 52 . Brenner tumors have been reported to show some cytomorphologic overlap with AGCTs, including round‐oval cells with frequent nuclear grooves, 53 but they usually express p63 and GATA3 54,55 and are negative for SCST markers 56 . SCTAT exhibits ring‐like tubular structures similar to Call‐Exner bodies in AGCTs, but they are commonly seen in patients with Peutz‐Jeghers syndrome 8,57 and harbor STK11 mutations 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Although they can express sex‐cord markers including SF‐1 and FOXL2, 51 they are also usually positive for epithelial and smooth muscle antigens and harbor NCOA1/NCOA2/NCOA3 rearrangements in 81% of cases 52 . Brenner tumors have been reported to show some cytomorphologic overlap with AGCTs, including round‐oval cells with frequent nuclear grooves, 53 but they usually express p63 and GATA3 54,55 and are negative for SCST markers 56 . SCTAT exhibits ring‐like tubular structures similar to Call‐Exner bodies in AGCTs, but they are commonly seen in patients with Peutz‐Jeghers syndrome 8,57 and harbor STK11 mutations 57 .…”
Section: Discussionmentioning
confidence: 99%
“…If AI could correctly predict whether a tumor is benign or malignant, it could help doctors avoid performing unnecessary and potentially risky biopsies on patients. Studies have shown that AI can accurately predict whether a brain tumor is benign or malignant [ 51 ] with 95% accuracy [ 52 ], which would avoid the need for biopsy [ 53 ]. PM initiatives are a step forward in cancer treatment, but they come with challenges.…”
Section: Introductionmentioning
confidence: 99%